Mobile Administrasi Desa Di Kantor Desa Kuala Utara Berbasis Android - Lepi, Andriyanto; Abd. Rahmat Karim Haba; Husdi; Sudirman S. Panna (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2024)
Abstract - The Kuala Utara Village Government still uses a manual system in the processing population administrations where administrative activities still require a long process for the people. On the other side, the village office is quite far away. So, many administrative activities are piled up so that people wait a long time for the process. An android-based village administration mobile system is required to improve the quality of administrative services to the community, especially in population administration processing activities. This research aims to simplify and speed up population administration activities by implementing an Android-based Village Administration Mobile application. In this case, it is to assist the needs of the community, in terms of administrative management using an Android smartphone. The results of this research are that this system helps the public in more effective and efficient administrative service activities and helps the public in making independent service requests by providing security facilities for users when starting this system. Keywords: Village Administration Mobile, Android, Community Access Ease